HUBUNGAN PRAKTIKUM TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PRA PANDEMI DAN SELAMA PANDEMI COVID-19: POTENSI LEARNING LOSS - Fatmawati Fatmawati (Biopedagogia, 2021)
Abstract: This study aimed to analyze the relationship between practicum and student learning outcomes in the pre-pandemic and during the Covid-19 pandemic. The research method applied is descriptive quantitative research which is supported by data collection techniques in the form of interviews, observations, and documentation. The research subjects are students of Biology Education, University of Borneo Tarakan. The results of data analysis showed that most of the practicums were carried out in the pre-covid-19 pandemic but only a few practicums were carried out during the pandemic with different practicum forms. This indicates the occurrence of learning loss in learning that practices science. Practicum is closely related to student learning outcomes. The relationship tends to be linear where student learning outcomes can increase in line with the quantity and quality of the practicum. Keywords:  Learning Outcomes, Learning Loss, Practicum